"Você é um menino ou uma menina?": A consciência de identidade transgênero - Silva, Carla Alves da (2006)
The purpose of this thesis is to discuss the journey towards identity awareness undertaken by the protagonists of the novels Stone Butch Blues, by Leslie Feinberg, and Middlesex, by Jeffrey Eugenides. On the surface, these two novels share a great deal from the point of view of gender studies: both depict female-born fiction characters whose identity construction is narrated in the first person and who tell us about their (re)position in the world, their awareness of being born "different", and most compellingly, their search to understand their own bodies, sex and gender. My intention is to test this apparent similarity against the preeminent theories about sex and gender, trying to establish my reflection from the viewpoint of queer and transgender theories.